The Anatomy of Financial Risk: A Legal and Economic Perspective on Hospital and Healthcare Management - Yofi Syarkani; Iwan Kusnawirawan; Hernayati Hernayati; Dwi Ratna Sari Handayan; Imam Waluyo (Jurnal Inovasi Global, 2025)
Financial and legal risk management in healthcare, particularly under national health insurance programs like Indonesia’s Jaminan Kesehatan Nasional (JKN), is critical for ensuring sustainable and high-quality care delivery. This study explores the multifaceted financial risks faced by hospitals, including rising operational costs, unpredictable patient volumes, inadequate reimbursement mechanisms, and delays in insurance payments. Additionally, it examines the legal frameworks governing billing practices, patient privacy, and fraud prevention, highlighting the consequences of non-compliance, such as financial penalties and reputational damage. Through a systematic literature review, this research identifies integrated risk management (IRM) strategies that combine financial, operational, and legal approaches to mitigate risks. Key strategies include implementing robust financial monitoring systems, strengthening legal compliance through staff training and audits, and advocating for policy reforms to address systemic gaps. Case studies from Indonesia and other countries illustrate the effectiveness of these strategies in improving financial sustainability and regulatory compliance. The findings underscore the importance of adopting IRM frameworks, investing in technology, and conducting further research to evaluate best practices. This study contributes to the growing body of literature by integrating economic and legal perspectives, offering actionable recommendations for healthcare systems operating under national health insurance programs.